2007
DOI: 10.1007/s00125-007-0603-6
|View full text |Cite
|
Sign up to set email alerts
|

A type 1 diabetes subgroup with a female bias is characterised by failure in tolerance to thyroid peroxidase at an early age and a strong association with the cytotoxic T-lymphocyte-associated antigen-4 gene

Abstract: Aims/hypothesis HLA haplotypes DRB1*03_DQB1*02 and DRB1*04_DQB1*0302, and allelic variation of the T cell regulatory gene cytotoxic T-lymphocyte-associated antigen-4 (CTLA4) and of the T cell activation gene protein tyrosine phosphatase, non-receptor type 22 (lymphoid) (PTPN22) have been associated with type 1 diabetes and autoimmune thyroid disease. Using thyroid peroxidase autoantibodies (TPOAbs) as an indicator of thyroid autoimmunity, we assessed whether the association of these loci is different in type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
4
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 38 publications
(85 reference statements)
8
53
4
4
Order By: Relevance
“…Idd5 is located on mouse chromosome 1 and has been shown by congenic strain analysis to consist of at least two loci, Idd5.1 and Idd5.2, positioned at the proximal and distal ends, respectively, of an ϳ15 Mb interval (3). Idd5.1 was defined as a 2.0 Mb B10-derived resistance interval containing four genes including the candidate genes Ctla4 and Icos (3,4), a remarkable finding since human T1D is associated with CTLA4 (5,6). In addition to the human T1D association with CTLA4, functional studies support the candidacy of Ctla4 as the diabetes gene in the Idd5.1 interval because the B10 allele of Ctla4 produces more of the "ligand-independent" splice form of CTLA-4 (liCTLA-4) than does the NOD allele (6).…”
Section: G Enes Termed Insulin-dependent Diabetes (Idd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Idd5 is located on mouse chromosome 1 and has been shown by congenic strain analysis to consist of at least two loci, Idd5.1 and Idd5.2, positioned at the proximal and distal ends, respectively, of an ϳ15 Mb interval (3). Idd5.1 was defined as a 2.0 Mb B10-derived resistance interval containing four genes including the candidate genes Ctla4 and Icos (3,4), a remarkable finding since human T1D is associated with CTLA4 (5,6). In addition to the human T1D association with CTLA4, functional studies support the candidacy of Ctla4 as the diabetes gene in the Idd5.1 interval because the B10 allele of Ctla4 produces more of the "ligand-independent" splice form of CTLA-4 (liCTLA-4) than does the NOD allele (6).…”
Section: G Enes Termed Insulin-dependent Diabetes (Idd)mentioning
confidence: 99%
“…For the sets of susceptibility genes in humans that can give rise to isolated T1D, not complicated with AITD disease or related autoantibodies, the CTLA4 SNPs are not associated, or only very weakly, with this subclass of T1D, and we proposed that this is due to the presence and function of human genes similar to Idd5.3 and Idd5.2/Nramp1 that can mask the effect of variation in the CTLA-4 gene. In the minor subgroup of T1D that is complicated with AITD or AITD autoantibodies, ϳ10 -15% of T1D cases, CTLA-4 genetic variation has a strong effect, presumably via its role in regulation of peripheral tolerance, in which the disease-associated CTLA4 haplotype is predisposing to a failure in tolerance to multiple organs or tissues (5). Our current results highlight the complexities of studying autoimmunity genes even in a well-controlled experimental model, and promote further caution in the design, execution, and interpretation of susceptibility gene mapping in humans.…”
Section: Human Gene Discovery and Disease Subclassificationmentioning
confidence: 99%
“…One well validated region associated with susceptibility to autoimmune disease harbors the CTLA4 gene on chromosome 2q33. An associated allele in this susceptibility region is the G allele of the SNP CT60 (rs3087243; A/G) in the CTLA4 gene region, which has been associated with risk to type 1 diabetes, Graves disease, autoimmune hypothyroidism, systemic lupus erythematosus, and Addison's disease (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The most widely accepted is the autoimmune genetic hypothesis, assuming involvement of genes associated with immune regulation [17]. Numerous observations have confirmed that genetic susceptibility is shared among autoimmune diseases, with the strongest association seen between T1DM and autoimmune thyroid disease (AITD) [11,12,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%